Dynamics of glycerine and water transport across human skin from binary mixtures - Ventura, S. A.; Kasting, G. B. (International journal of cosmetic science, 2017)
Objective Skin transport properties of glycerine and water from binary mixtures contacting human skin were determined to better understand the mechanism of skin moisturization by aqueous glycerine formulations. Methods Steady‐state permeation for 3H2O and 14C‐glycerine across split‐thickness human skin in vitro and desorption dynamics of the same permeants in isolated human stratum corneum (HSC) were experimentally determined under near equilibrium conditions. These data were compared to a priori values developed in the context of a thermodynamic model for binary mixtures of glycerine and water and a previously determined water sorption isotherm for HSC. This allowed the estimation of diffusion and partition coefficients for each permeant in the HSC, as well as HSC thickness, as a function of composition of the contacting solution. These data may be used to estimate water retention and associated HSC swelling related to the absorption and slow release of glycerine from the skin. Results It took 6+ days for glycerine to completely desorb from HSC immersed in glycerine/water binary solutions. Desorption of both 3H2O and 14C‐glycerine from HSC was slower in pure water than from binary mixtures, a result that is largely explained by the greater swelling of HSC in water. Parametric relationships were developed for water and glycerine intradiffusivities in HSC as functions of HSC water content, and a mutual diffusion coefficient was estimated by analogy with glycerine/water binary solutions. The intradiffusivity of 14C‐glycerine in HSC as inferred from sorption/desorption experiments was shown to be approximately 10‐fold less than that inferred from permeation experiments, whereas the corresponding values for 3H2O were comparable. Conclusion These studies confirm that glycerine enters HSC in substantial quantities and has a long residence time therein. The coupling between bulk water and glycerine transport projected from binary solution data suggests the net effect of glycerine is to slow water loss from the skin. The data support the concept of glycerine as a humectant with an excellent balance of skin penetration and retention characteristics; however, they do not rule out the possibility of an additional biological effect on skin barrier homoeostasis. Résumé Objectif Les propriétés de transport transcutané de la glycérine et de l'eau à partir de mélanges binaires en contact avec la peau humaine ont été déterminées afin de mieux comprendre le mécanisme d'hydratation de la peau par des formulations aqueuses de glycérine. Methodes Nous avons déterminé expérimentalement l’état d’équilibre de perméation pour 3H2O et 14C‐glycérine à travers la peau humaine in vitro et la dynamique de désorption des mêmes perméants dans le stratum corneum humain (HSC) isolé dans des conditions près de l’équilibre. Ces données ont été comparées aux valeurs a priori développées dans le cadre d'un modèle thermodynamique pour les mélanges binaires de la glycérine et de l'eau et un isotherme de sorption d'eau précédemment déterminée pour le HSC. Cela a permis l'estimation des coefficients de diffusion et de partage pour chaque perméant dans le HSC, ainsi que l’épaisseur du HSC, en fonction de la composition de la solution mise en contact. Ces données peuvent être utilisées pour estimer la rétention d'eau et le gonflement du HSC associé, liés à l'absorption et la libération lente de la glycérine de la peau. Résultats Il a fallu 6+ jours pour la glycérine pour désorber complètement du HSC immergé dans des solutions binaires glycérine/eau. La désorption des deux 3H2O 14C‐glycérine du HSC a été plus lente dans l'eau pure à partir de mélanges binaires, un résultat qui est en grande partie expliquée par le plus grand gonflement du HSC dans l'eau. Des relations paramétriques ont été développées pour les intradiffusivités de l'eau et de glycérine dans le HSC en fonction de la teneur en eau, et un coefficient mutuel de diffusion a été estimé par analogie avec les solutions binaires glycérine/eau. L’ intradiffusivité de 14C‐glycérine dans le HSC telle que déduite à partir des expériences de désorption a été montrée être environ dix fois inférieure à celle déduite des expériences de perméation, alors que les valeurs correspondantes pour 3H2O étaient comparables. Conclusion Ces études confirment que la glycérine pénètre le HSC en quantités substantielles et possède une longue rémanence dans celui‐ci. Le couplage entre l'eau en vrac et le transport de la glycérine extrapolé à partir des données des solutions binaires suggère que l'effet net de la glycérine est de ralentir la perte d'eau de la peau. Les données soutiennent le concept de la glycérine comme humectant avec un excellent équilibre des caractéristiques de pénétration de la peau et de rétention; cependant, ils ne exclurent pas la possibilité d'un effet biologique supplémentaire sur la barrière cutanée en homéostasie. Glycerine enters the stratum corneum in substantial quantities when applied to skin from aqueous formulations. It has a surprisingly long residence time ‐‐ greater than six days according to our measurements ‐‐ and it holds water due to its humectancy during that time. These properties make it an excellent skin moisturizer.